1995
DOI: 10.1111/j.1559-1816.1995.tb01829.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Friends' and Parental Smoking on Adolescent Smoking Behavior: The Effects of Time and Prior Smoking1

Abstract: This research examines the relative importance of parental and friends' influences on adolescents' smoking behavior and changes in the effects of social influences during adolescence. Data were collected at 4 times from 7th to 9th grades. Random‐effects ordinal regression models were employed to predict the repeated classification of adolescent smoking status using time effects, prior smoking status, friends' smoking, and parental smoking. In general, the effects of friends' smoking are stronger than those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
77
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 48 publications
21
77
1
1
Order By: Relevance
“…This is consistent with the conclusions in Hu et al (1995), wherein parental influence may be more salient in Asian American populations relative to other ethnic groups. Further research is warranted to expand on these findings by examining the influence of parental genotype as a potential moderator or mechanistic factor explaining the influence of parental history of alcohol problems on alcohol use and problems among Asian American young adults.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the conclusions in Hu et al (1995), wherein parental influence may be more salient in Asian American populations relative to other ethnic groups. Further research is warranted to expand on these findings by examining the influence of parental genotype as a potential moderator or mechanistic factor explaining the influence of parental history of alcohol problems on alcohol use and problems among Asian American young adults.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, this study examined parental alcohol use (representing FH of alcohol misuse), as it has been linked to adolescent and young adult alcohol consumption among Asian Americans (Hendershot et al, 2005;Shih et al, 2010). In the general population, parental alcohol use has been shown to be a significant predictor of adolescent drinking (White et al, 2000); however, this effect was found to be particularly strong among Asian American adolescents (De Moor et al, 1989;Hu et al, 1995).…”
mentioning
confidence: 99%
“…Showing that expectancies do not mediate the influence of four relatively weak predictors of smoking behavior cannot be considered a fair test of the expectancy-mediation hypothesis. In the present study we addressed this limitation by including three distal variables identified by previous research as being moderate to strong predictors of future adolescent smoking: (a) peer smoking, (b) parent smoking, and (c) current smoking status of the respondent (Biglan et al, 1995;Chassin et al, 1996;Conrad et al, 1992;Hu et al, 1995;Millar & Hunter, 1990).…”
Section: Smoking Expectancies As Mediatorsmentioning
confidence: 99%
“…Although the expectancy mediation hypothesis appears to be widely accepted in the literature, direct empirical tests have been rare. In the present study we investigated whether smoking expectancies mediate the effects of three factors previously shown to predict adolescent smoking intentions: (a) peer smoking, (b) parent smoking, and (c) respondents' current smoking status (Biglan, Duncan, Ary, & Smolkowski, 1995;Chassin, Presson, Rose, & Sherman, 1996;Conrad, Flay, & Hill, 1992;Hu et al, 1995;Millar & Hunter, 1990). Furthermore, to determine whether these mediational effects generalize across different measurement approaches, we compare the mediational properties of four operationalizations of the smoking expectancy construct.…”
mentioning
confidence: 99%
“…Generalmente, las chicas son más vulnerables que los muchachos a la influencia tabáquica de los pares, lo cual puede deberse a que las relaciones sociales entre chicas tienden a ser más íntimas y exclusivas, pasan más tiempo con amigos y están más involucradas en la vida de sus pares (Hu, Flay, Hedeker, Siddiqui y Day, 1995).…”
Section: Introducción Lunclassified